THE EXTENT OF THE MATURITY OF THE IMPLEMENTATION OF E-GOVERNMENT AT THE LOCAL LEVEL IN INDONESIA: A LITERATURE REVIEW BASED ON SPBE EVALUATION - Nugraha, Budi; Andriwiguna, Adhy; Genedin, Triananda (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2026)
This study examines the maturity of e-government implementation in Indonesian local governments using a systematic literature review guided by the national Electronic-Based Government System (SPBE) framework. Data sources include peer-reviewed journal articles, SPBE evaluation reports, and the United Nations E-Government Development Index (EGDI) from 2018 to 2024. The findings indicate an improvement in Indonesia’s national SPBE score from “fair” (2.34 in 2022) to “good” (2.79 in 2023), accompanied by a remarkable rise in EGDI ranking from 107th (2018) to 64th (2024). Nevertheless, significant disparities persist across regions. Key enablers of progress are regulatory clarity, strong local leadership, continuous capacity-building programs, and cross-sector system integration, while major barriers include inadequate infrastructure, low digital literacy among civil servants, and overlapping regulations. The study contributes to e-government scholarship by explicitly linking local performance variations to the SPBE evaluation domains and provides practical policy implications through a roadmap of competency-based training, data governance, and regulatory harmonization. These findings offer actionable guidance for policymakers to accelerate inclusive digital transformation and achieve the national SPBE “Excellent” target.